Identifying Hotspots of Transport Disadvantage and Car Dependency in Rural Ireland - Caulfield, Brian (My University, 2021)
This paper explores the concepts of car dependency and transport disadvantage and the correlation between them in rural Ireland as a means of highlighting incidences of possible forced car ownership with the use of Geographical Information Systems (GIS). Societal and cultural challenges associated with the prevalence of the private car as the primary or in some cases the only form of mobility for people living in rural areas are examined resulting in potential cases of forced car ownership (FCO). Those defined as being forced to own a car are those who may find themselves in circumstances with low transport accessibility and low income, which is intensified by the need to economically participate in society for financial gain . This paper examines the existing gap between the necessity of transport and the provision of reliable public transport in rural Ireland, which is frequently attributed as a major determinant of FCO in the literature. While it is acknowledged that forced car ownership similarly exists in urban areas under the same or similar conditions, this paper focuses exclusively on the incidence of FCO in rural areas due to potentially higher levels of car dependency. The main objective of this paper is to identify hotspots or areas that are susceptible to increasing rates of FCO and transport disadvantage. Using the information gained from identifying the locations of these hotspots, transport planners and policymakers can tailor interventions to improve sustainable mobility in these areas and address equity concerns.
PUBLISHED
Keywords: Equity; Rural transport; Spatial analysis; Smart & Sustainable Planet; Transport; Transport